Potential of Laurencia obtusa as a substrate for the development of a probiotic Saccharomyces cerevisiae - Caf, F.; Yilmaz, O.; Sen Ozdemir, N. (C M B Assoc, 2017)
Laurencia obtusa (Ceramiales, Rhodophyta) has tremendous nutritional value, being high in proteins, oligosaccharides, vitamins, essential minerals, and fatty acids, and it is a rich source of amino acids and trace elements. In this study, L. obtusa was extracted and subjected to phenolic, sugar and flavonoid analyses. The fatty acid, vitamin and phytosterol contents in Saccharomyces cerevisiae were evaluated when it was incubated with L. obtusa dry biomass. The fatty acids in the lipid extract were analysed after converting them into methyl esters using gas chromatography, and vitamin concentrations were measured using high-performance liquid chromatography (HPLC). According to the achieved results, the total fatty acid levels and vitamin contents of the S. cerevisiae prepared with algal extract increased at different rates. Our results showed that alpha-tocopherol decreased in the group in which the S. cerevisiae was added the algal extract. When compared to the control group, ergesterol increased in the group in which L. obtusa extract was added. Additionally, when compared to the control group in which L. obtusa extract was added, stearic acid (18: 0), oleic acid (18: 1) and linoleic acid (18: 2) increased in the other groups. Palmitoleic acid (16: 1) increased in the L. obtusa culture medium, but palmitic acid decreased in the L. obtusa culture medium. In conclusion, it was determined that the L. obtusa extract added to the development medium of S. cerevisiae caused differences in the synthesis of some vitamins and fatty acids.
Keywords: Fatty acids; Nutritional value; Probiotic/prebiotic; Laurencia obtusa; Saccharomyces cerevisiae